Spark : how creativity works - Burstein, Julie. (Harper, 2011)
How did Richard Ford's cat influence his work as a novelist? How is Chuck Close's portraiture driven by his inability to remember faces? What pivotal moment helped Rosanne Cash understand the healing power of the stage? Creativity is an elusive subject. We enjoy its fruits--movies, novels, paintings, songs--but rarely are we privy to what happens in the creative process. In Spark, journalist Julie Burstein traces the roots of some of the twenty-first century's most influential and creative thinkers, including Joyce Carol Oates, Yo-Yo Ma, David Milch, Isabel Allende, and Joshua Redman. Burstein pulls back the curtain to reveal the sources of these artists' inspiration and the processes that bring their work into being. "These artists may not change lead into gold," Burstein writes, "but they lift materials from their familiar contexts, combining, reshaping, transforming them into works of art that change the way we see the world."--From publisher description.